Applications of deep learning and big IoT on personalized healthcare services - Wason, Ritika 1982-; Goyal, Dinesh 1976-; Jain, Vishal 1983-; Balamurugan, S. 1985- (IGI Global, 2020)
"This book explores the different applications of deep learning algorithms in implementing big data and IoT enabled smart solutions for personalized healthcare services"--
Description based on title screen (IGI Global, viewed 04/15/2020)
Keywords: Deep Learning; Personal Health Services; Internet; Big Data; Medical informatics; Medical care; Big data; Internet of things